African American Parents' Perceived Vaccine Efficacy Moderates the Effect of Message Framing on Psychological Reactance to HPV Vaccine Advocacy. Issue 8 (3rd August 2021) - Richards, Adam S.; Qin, Yan; Daily, Kelly; Nan, Xiaoli
Abstract : This experiment assessed how the frame of promotional vaccine messages elicited psychological reactance differently for African American parents according to their level of perceived vaccine efficacy. We found that those with low perceived HPV vaccine efficacy experienced more psychological reactance in response to loss-framed messages compared to gain-framed messages, whereas message framing made little difference for those with high perceived HPV vaccine efficacy. In addition, the interaction between frame and perceived HPV vaccine efficacy indirectly affected parents' intentions to vaccinate their child for HPV via reactance. These results support current theorizing about framing effects under defensive message processing specifically as it applies to psychological reactance.